Implementasi Reaktor Biogas Berbasis Komunitas untuk Kemandirian Energi dan Keberlanjutan Lingkungan di Desa Pesisir Sulawesi Selatan - Amiruddin, Amiruddin; Baharuddin, Fiskia Rera; Mudarris, Mudarris; Hidayat, Akmal; Basirung, Muhammad Romario (Bengkulu Institute, 2025)
This community service program aims to implement a community-based biogas reactor as an alternative energy solution and sustainable livestock waste management system in Laikang Village, Mangarabombang District, Takalar Regency, South Sulawesi, Indonesia. The main problems faced by the partner community were the accumulation of cattle manure causing environmental pollution and the high dependence on subsidized liquefied petroleum gas (LPG). The program was carried out for eight months using a participatory and appropriate technology approach, involving the community at every stage, including planning, reactor construction, technical training, and performance evaluation. A 6 m³ anaerobic biogas reactor was successfully designed, built, and operated using cattle manure and water in a 1:1 ratio. Field measurements showed that the reactor produced 1.0–1.2 m³ of methane gas per day, replacing approximately 30–35% of household LPG consumption. The fermentation process also produced 10–15 liters of slurry per day, which was further utilized as liquid organic fertilizer. The program’s impact includes a 70% reduction in open livestock waste, 30% reduction in household energy costs, and the establishment of a Village Energy Self-Reliance Group (Kelompok Energi Mandiri Desa – KEMD) responsible for long-term management of the biogas system. The results demonstrate that community-based biogas technology effectively promotes rural energy independence, environmental awareness, and local economic empowerment. This initiative aligns with the Sustainable Development Goals (SDGs), particularly Goal 7 (Affordable and Clean Energy) and Goal 13 (Climate Action). The implemented model can serve as a replicable prototype for other coastal and rural communities in Indonesia with similar livestock and energy challenges.